Budidaya Ikan Kerapu (Serranidae) pada Keramba Jaring Apung (KJA) - Langkosono Langkosono (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2007)
Groupers are commercial fish belonging to Serranidae family.  Some species such as barramundi cod (Cromileptes altivelis) and flowery cod (Epinephelus fuscoguttatus) have been cultured in floating net cages. This study was carried out to determine the growth rate in terms of length and weight of both species as well as water quality of coastal Kombal Bay, West Pemenang Village, West Lombok. The results showed that the growth rate of both species was approximately the same as each other. Nevertheless, the weight increase of flowery cod seemed to be slightly faster than that of barramundi cod. Water quality in the location of the fish culture supported sufficiently  the growth of both grouper species.